Blood Profile of Rattus Nurvegicus Exposed to HgCl2 and Received Combination of IR Bagendit Rice Leaves-Infused Water and Young Coconut Water - Budi Santosa (Medical Laboratory Technology Journal, 2022)
Mercury chloride (HgCl2) is widely used in industries; in fact, this chemical substance is deadly for health and causes various health problems, such as liver damage, kidney damage, and hematopoietic disorders, especially in erythropoiesis. This study aims to determine the blood profile in Rattus nurvegicus exposed to HgCl2 by combining IR Bagendit rice leaves-infused water and young coconut water. This study employed an experimental method to examine the positive control group exposed to HgCl2 and the negative control group receiving a placebo. Meanwhile, the treatment groups received a combination of IR Bagendit rice leaves-infused water in stratified compositions and young coconut water. The hematologic profile was examined using a hematologic analyzer, while the reticulocyte count was examined using wet and dry methods. The mean value of each group was tested using ANOVA. This study has successively obtained average levels of Hb (C+ 12,0;C- 14,2;T1 12,5;T2 12,9;T3 12,8), the erythrocyte count (C+ 6,52;C- 7,80;T1 1,44;T2 1,07;T3 7,32), levels of Ht (C+ 35,5;C- 42,9;T1 37,8;T2 37,9;T3 38,2), MCV (C+ 73,7;C- 79,9;T1 80,4;T2 78,7;T3 79,6), MCH (C+ 27,3;C- 29,9;T1 29,5;T2 28,5;T3 29,1), and MCHC (C+ 31,1;C- 34,2;T1 31,9;T2 33,3;T3 32,1), and the reticulocyte count (C+ 2,0;C- 1,2;T1 1,3;T2 1,1;T3 1,3). The significant differences in the groups are found in levels of Hb, Ht, MCV, and MCHC (p-value 0,00; 0,00; 0,03; 0,01). This study concludes that combining IR Bagendit rice leaves-infused water and coconut water could prevent blood profile exposure to HgCl2. Suggestions for further research to increase the intervention time and measure oxygen levels.